Timescapes beyond the Metropolises: Culture-led urban regeneration in Myllytulli, Oulu - Hotakainen, Tiina (Aalto ARTS Department of Architecture, Tampere University School of Architecture and Oulu School of Architecture., 2021)
The past decades have witnessed a rise of culture-led urban regeneration. The successful cultural models have travelled throughout the world, and applied to cities and urban areas regardless of their size and location. Culture, ranging between high culture and contemporary creative economies, acquires potential to contribute to physical, social and economic aspects of urban regeneration. Successful examples of culture-led urban regeneration have tempted small cities to invest in traveling global cultural policies. Academic community has criticized these travelling policies for over-simplifying the abstract notion of culture, overrating the benefits of culture-led urban regeneration and ignoring local temporal specifics. This paper argues that a temporal analysis framework would enable a holistic approach to culture-led urban regeneration, and embrace the temporal uniqueness of urban contexts. This article discusses the temporal characteristics of culture-led regeneration in a provincial city context within an empirical case study analysis of Myllytulli in Oulu, Northern Finland. Myllytulli represents a district of regional cultural relevance where cultural amenities range from museums and educational facilities to creative bottom-up initiatives. This study reframes Myllytulli’s urban regeneration process using temporal conceptions of recent interdisciplinary academic discourse. The empirical data set consists of expert interviews, observation material and municipal planning documents. The results analyse the urban regeneration process within the linear temporal ideals of rational-comprehensive planning, reactive experiential urbanism and relational dimensions of time. The paper suggests time-sensitive approaches for future research and practice of urban regeneration.